KEUNGGULAN KOMPARATIF TEKSTIL DAN PRODUK TEKSTIL INDONESIA TERHADAP TIONGKOK DALAM ASEAN-CHINA FREE TRADE AREA: TANTANGAN BAGI INDONESIA - Annisa Nova Widyastuti (UIR Press, 2020)
The focus of this study is the challenges of Indonesian Textile and Textile Product (TPT) to China in the framework of ASEAN-China Free Trade Area (ACFTA) which seen from the comparative advantage. Theoritically, ACFTA should have a positive impact for the members since there is a tariff removal to 0%. TPT is one of the industries that has a large contribution to Indonesia’s trade. However, TPT from China dominates over local TPT. The purpose of this study is to find out challenges of Indonesian TPT in the ACFTA framework. This research was done by qualitatively in explanative design. The results of this study are the difficulty of obtaining raw materials, outdated production machine, the difficulty of applying Indonesia National Standard to the textile industry and high loan prime rate. These are the main challenges for Indonesian textile products. This research shows that Indonesia doesn't have the comparative advantage yet. Therefore, the strategy of the government as well as the TPT producers is needed in facing the challenges so it would improve the competitiveness of the Indonesian textile industry